PENINGKATAN 'NILAI KALOR (Kal/g) KULIT DURIAN SESUDAH MENJADI BRIKET BIOARANG (Studi Pemanfaatan Sampah Kulit Ourian Sebagai Alternatif Pembuatan Briket Bioarang) - Olivia Agustin Nadia; Waluyo Jati; Umi Rahayu (Poltekkes Kemenkes Surabaya, 2014)
The presence of organic trash heap especially durian peels was very abundance when harvesttime. To decreasing trash from durian peels it could be used as biocharcoal briquette. The making ofbiocharcoal briquette by using starch glue addition and water as source to increasing kalor value. Thisresearch purpose to recognize how much kalor value increase in durian peel.This research as research type is Quasi Experiment Design with One Group Pre-Post TestDesign research, namely this design only using one subject group and also make measurement beforeand after provide treatment on subject.The analysis result of tapioca flour addition indicating that give different concentration on heatvalue increase in durian peels. Based on the yield result had be done state that dry durian peel obtainedas many 3863,33 kal/g. While, heat value in durian peel already processed become biocharcoal briquettewith tapioca flour addition 1% gained average result 4047,46 kallg, tapioca flour addition 2% gainedaverage result 4225,25 kal/g, and tapioca flour addition 3% gained average result 4546,11 kal/g.There improvement on heat value of dry durian peel and had already processed becomebiocharcoal briquette. The increase of heat value (kal/g) gained different result according to tapioca flouraddition and water 100 mililiter that are 1%, 2%, and 3%. Suggested that must be done further research tomake biocharcoal briquette is not only durian peel but also other organic trash heap to rise up kalor value(kal/g) and help to reduce organic trash heap then could be advantage for the people mainly durianmerchants.